Current global research on mandibular defect: A bibliometric analysis from 2001 to 2021 - Li, Yongdi; Li, Duchenhui; Tang, Zhenglong; Wang, Dongxiang; Yang, Zhishan; Liu, Yiheng (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Mandibular defects can result from congenital deformities, trauma, tumor resection, and osteomyelitis. The shape was irregular because the lower jaw was radians. This involves teeth and jaw functions; therefore, the difficulty of bone repair is greater than that in other body parts. Several standard treatments are available, but they result in various problems, such as difficulties in skin flap transplantation and possible zone dysfunction, artificial material boneless combining ability, and a long treatment period. This study aimed to introduce the present status of research on mandibular defects to analyze the current introduction and predict future research trends through a bibliometric study. Methods: From 2001 to 2021, publications on mandibular defects were collected for bibliometric visualization using VOSviewer, CiteSpace, and Scimago Graphica software based on the Web of Science Core Collection. Results: This study analyzed 4,377 articles, including 1,080 published in the United States, 563 in China, and 359 in Germany, with an increase in the number of articles published over the past 20 years. Wikesjoe and Ulf Mai E had the most publications (p = 36) and citations (citations = 1,553). Shanghai Jiaotong University published the highest number of papers among the research institutions (p = 88). The most productive journal was Journal of Oral and Maxillofacial Surgery, and the cited literature was primarily classified as dentistry, dermatology, and surgery. Cluster Analysis of Co-occurrence Keywords revealed that highest number of core words were mandibular defects, mandibular reconstruction, and bone regeneration. The highest cited words were head and neck cancer, accuracy, and osteogenic differentiation. High-frequency terms of Cluster Analysis of References were osteosynthesis plate, tissue engineering, and rapid distraction rate. Conclusion: Over the past 20 years, the number of studies on mandibular defects has gradually increased. New surgical procedures are increasingly being used in clinical practice. Current frontier topics mainly focus on areas such as computer-aided design, 3D printing of osteotomy and reconstruction guide plates, virtual surgical planning, and bone tissue engineering.